Determinant socio-factors to rehabilitate mangrove forests in Mangunharjo Village, Semarang City - Adhe Viana Yulida Putri; Ronggo Sadono (Forest Science and Technology, 2025)
Mangrove forests play an important role in climate change mitigation and have attracted significant attention from scholars, governments, businesses, and non-governmental organizations. Therefore, this study aims to (1) describe land cover changes caused by rehabilitation activities and (2) investigate the dominant factors affecting mangrove improvement through rehabilitation activities. Land cover changes were monitored using Landsat 5 TM, Landsat 7 ETM+, and Landsat 9 OLI/TRIS. The images obtained were then classified using the Normalized Difference Vegetation Index (NDVI). Interviews with 35 respondents were conducted to investigate the dominant factors affecting mangrove improvement, which were then analyzed using factor analysis and the principal component analysis method. The results showed that mangrove land cover increased by 50.09 ha between 1998 ̶ 2024. The dominant factors during rehabilitation activities were classified into 2 groups, namely internal factors of farmers and external factors. Internal factors included education, technology skills, knowledge of mangrove ecosystems, and age. Meanwhile, the external factors included the intensity of assistance by organizations and group members’ participation. Based on these results, information on the dominant factors contributing to rehabilitation success could improve mangrove forests in Mangunharjo Village.